Clinical Outcomes of Frozen-Thawed Embryos Generated From Growth Hormone Stimulation in Expected Poor Responders - Zhu, Jinliang; Wang, Ying; Chen, Lixue; Liu, Ping; Li, Rong; Qiao, Jie (Frontiers in Endocrinology, 2021)
Objective: This study aimed to elucidate whether growth hormone (GH) adjuvant therapy significantly improves clinical outcomes for expected poor responders in frozen-thawed cycles. Methods: Expected poor responders undergoing controlled ovarian stimulation with or without GH adjuvant therapy, and subsequently underwent the first frozen-thawed transfer from January 2017 to March 2020 were retrospectively reviewed. Maternal age was matched at a 1:1 ratio between the GH and control groups. All statistical analyses were performed with the Statistical Package for the Social Sciences software. Results: A total of 376 frozen-thawed cycles comprised the GH and control groups at a ratio of 1:1. The number of oocytes (7.13 ± 3.93 vs. 5.89 ± 3.33; p = 0.001), two pronuclei zygotes (4.66 ± 2.76 vs. 3.99 ± 2.31; p = 0.011), and day 3 available embryos (3.86 ± 2.62 vs. 3.26 ± 2.04; p = 0.014) obtained in the GH group was significantly higher than the control group in corresponding fresh cycles. The clinical pregnancy (30.3% vs. 31.0%; p = 0.883), implantation (25.3% vs. 26.2%; p = 0.829), early abortion (16.1% vs. 15.8%; p = 0.967), and live birth rates (20.6% vs 20.8%; p=0.980) were comparable between the two groups in frozen-thawed cycles. Interestingly, improvement in the clinical pregnancy (46.8% vs. 32.1%; p = 0.075), early miscarriage (10.3% vs. 20.0%; p = 0.449), and live birth rates (35.7% vs. 18.9%; p = 0.031) was found in the subgroup of PORs with good quality blastocyst transfer (≥4BB) following GH co-treatment. Conclusions: GH administration would increase oocyte quantity and quality, in turn, improve live birth rate in PORs